Scleromyositis: A distinct novel entity within the systemic sclerosis and autoimmune myositis spectrum. Implications for care and pathogenesis - Giannini, Margherita; Ellezam, Benjamin; Leclair, Valérie; Lefebvre, Frédéric; Troyanov, Yves; Hudson, Marie; Senécal, Jean-Luc; Geny, Bernard; Landon-Cardinal, Océane; Meyer, Alain (Frontiers in Immunology, 2023)
Systemic sclerosis and autoimmune myositis are both associated with decreased quality of life and increased mortality. Their prognosis and management largely depend on the disease subgroups. Indeed, systemic sclerosis is a heterogeneous disease, the two predominant forms of the disease being limited and diffuse scleroderma. Autoimmune myositis is also a heterogeneous group of myopathies that classically encompass necrotizing myopathy, antisynthetase syndrome, dermatomyositis and inclusion body myositis. Recent data revealed that an additional disease subset, denominated “scleromyositis”, should be recognized within both the systemic sclerosis and the autoimmune myositis spectrum. We performed an in-depth review of the literature with the aim of better delineating scleromyositis. Our review highlights that this concept is supported by recent clinical, serological and histopathological findings that have important implications for patient management and understanding of the disease pathophysiology. As compared with other subsets of systemic sclerosis and autoimmune myositis, scleromyositis patients can present with a characteristic pattern of muscle involvement (i.e. distribution of muscle weakness) along with multisystemic involvement, and some of these extra-muscular complications are associated with poor prognosis. Several autoantibodies have been specifically associated with scleromyositis, but they are not currently integrated in diagnostic and classification criteria for systemic sclerosis and autoimmune myositis. Finally, striking vasculopathic lesions at muscle biopsy have been shown to be hallmarks of scleromyositis, providing a strong anatomopathological substratum for the concept of scleromyositis. These findings bring new insights into the pathogenesis of scleromyositis and help to diagnose this condition, in patients with subtle SSc features and/or no autoantibodies (i.e. “seronegative” scleromyositis). No guidelines are available for the management of these patients, but recent data are showing the way towards a new therapeutic approach dedicated to these patients.